(untitled) (The Review of Diabetic Studies, 2025)
Quinazoline semicarbazone derivatives were synthesized by condensation of quinazoline semicarbazide with different aromatic carbonyl compounds (Isatin, Camphor, Benzophenone, p-dimethyl amino benzaldehyde and Vanillin). The synthesized compounds were characterized by physicochemical determination and their purity was evinced by TLC. Their structures were confirmed by IR, 1H NMR, UV spectroscopy and elemental analysis.